The provision of health services as a development initiative by Local Authorities: the case of Chegutu Rural District Council - Makiyi, Beatrice E. (Midlands State University, 2018)
The research sought to explore that provision of health services can be used as a solution to development challenges thus enabling the improvement of the lives of the rural people. Local Authorities who have adopted provision of health services have been treating it as a social goal and not a development goal hence in turn they have been failing to implement successful development initiatives in rural areas. The research was based on one broad objective which is to establish the extent to which provision of health services can be used to improve the living conditions of the rural people and sub objectives which were to highlight the importance of the relationship between health services and development ,to identify the extent to which the health service provision can improve the living conditions of the rural people ,challenges being faced in implementing this development initiatives and to establish possible mechanisms that can be utilised to address the challenges .health and development has been viewed by various scholars as a cornerstone for development in which they highlighted that when an individual is healthy ,they can perform better ,develop to their full capabilities be productive and earn for themselves .The absence of good health will lead people into poverty traps thereby promoting high death rate in the society. Economic development without improvement on the well being of the people is considered a waste because development should be able to target the health of the people first and make it a priority. To improve the lives of the rural people the health services should not benefit the rich only but the poor, the disabled and those living in hard to reach areas that are usually left out so that they equally benefit from healthcare.to further discuss the literature theoretical framework based on the livelihood approach, dualistic development theory and the capability approach was adopted for the study. The research used qualitative and quantitative approaches to research and data was collected using in depth interviews, questionnaires and observations to collect information from village health workers, Chegutu Rdc employees and health staff, community members, community leaders and councillors. A case study was adopted for the study examining the position of Chegutu Rdc towards provision of health services .The population size used for Chegutu Rural District was 110 000, 2 699 as the target population and a sample size of 85. The researcher used sampling techniques like simple random sampling, convenience and purposive sampling to select the sample for the research .The research findings deduced that the provision of health services is relevant to the development needs of the rural people in Chegutu Rural District as the majority of them echoed that indeed the provision of health services has managed to alleviate their hardships despite that the clinical services are still of poor quality. However those in hard to reach areas and resettlement areas most the elderly, children and pregnant women still lead impoverished lives with deteriorating health due to limited access to healthcare. The research then concluded that for the lives of the rural people to improve there is need for provision of more health centres for improved access as well as ensuring that every social group in the society benefits from the health services. The health services have to be improved as well as the participation of the people in issues concerning their health and development .the research also detected that the health budget is little hence the council is confronted by lack of funding which has promoted poor quality, unavailability of drugs in clinics, lack of a mobile clinic to mention but a few. Given this the research then made recommendations which include the increasing of the health budget so that the council may be able to effectively finance the provision of health services and the need to link development goals and health service provision so that targeted development goals.